Monitoring Kadar Air Berdasarkan Kadar pH, Tingkat Kondusifitas Air, dan Kadar Kekeruhan Air - Febriansyah, Aan; Irwan, Irwan; Surojo, Surojo; Zahri, Apriadi; Amanda, Dea (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
This research leads to monitor condition of cleanliness and suitability of clean water is very important to support human life daily. Clean water will make us feel safe and comfortable when using it. There are several particles and materials contained in water, even in the clean water category. Several parameters that are often measured as benchmarks for the level of water cleanliness include the acidity level of the water (pH level), the number of particles or substances in the form of organic and non-organic compounds in the water or often called TDS (Total Dissolve Solid) and the level of water turbidity or often called turbidity. In this research, monitoring will be carried out on water located on the coast, for example brackish water, on the levels of these three water parameters so that the water can be categorized as suitable for use at least for MCK (Bathing Washing Toilet) for people who use this water. In this research, a filter method was used to purify water using palm fiber, silica sand, zeolite stone and activated charcoal. Several test results carried out showed an increase in the acidity level of the water from 6.4 NTU to 6.78 NTU, a decrease in the level of impurities in the water or TDS from 1180 ppm to 1104 ppm and a decrease in the level of water turbidity or turbidity from 3.2 to 1.16. The test data shows that the filter can work quite well even though the decrease that occurs is not very significant, especially in the TDS level value and this value can be monitored well on the LCD or on the smartphone application.